Application of Data Mining Classification C4.5 Patient Satisfaction with Tuan Rondahaim Simalungun Hospital Service - Nadrah Fauziah; Muhammad Ridwan Lubis; Bahrudi Efendi Damanik (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
The purpose of this study was to produce a measuring instrument for patient satisfaction with hospital services. In order to further improve patient care. The method used in this study is the C4.5 Algorithm, where the data source used is a questionnaire/questionnaire technique which is given a questionnaire to the general public who visit the hospital. The results of this study are expected to provide input to the Tuan Rondahaim Hospital in Simalungun by using the C4.5 Algorithm. This can be done by using a decision tree model or decision tree in the C4.5 algorithm. In this study, the researchers used data from the patients of RSUD Tuan Rondahaim, totaling 105 patients through a questionnaire that the researchers distributed. The variables are Hospital Place (C1), Empathy (C2) and Responsiveness (C3). The testing process of this study uses Rapid Miner software to generate rules and a decision tree model or decision tree that will be used in determining the patient satisfaction factor for Tuan Rondahaim Hospital. The results of this study obtained 14 rules with an accuracy rate of 93.55%.